2018
DOI: 10.1080/02642069.2018.1534962
|View full text |Cite
|
Sign up to set email alerts
|

Over and over: local fans and spectator sport tourist engagement

Abstract: This study investigates consumer engagement within the live sport-as-service industry by exploring the match-day experiences of spectator sport tourists. It highlights the importance of authentic and sincere experiences manifest through tourists' interactions with local fans. Data was collected via semi-structured interviews with international tourists who had visited Glasgow and attended a Celtic FC match. The findings demonstrate that football clubs may overlook the importance of consumer engagement, and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Hence, managers must endeavor to gain a more in-depth understanding of why some travelers may opt to behave in an unpleasant and inappropriate fashion within the highly regulated and complex airport environment. This echoed extant research, which highlights the substantive impact that the social environment can have on travel experiences (Cordina, Gannon and Croall 2019). The results emerging from Airport B suggested that misbehavior and dissatisfaction partly stem from poor employee service.…”
Section: Practical Implicationsmentioning
confidence: 70%
“…Hence, managers must endeavor to gain a more in-depth understanding of why some travelers may opt to behave in an unpleasant and inappropriate fashion within the highly regulated and complex airport environment. This echoed extant research, which highlights the substantive impact that the social environment can have on travel experiences (Cordina, Gannon and Croall 2019). The results emerging from Airport B suggested that misbehavior and dissatisfaction partly stem from poor employee service.…”
Section: Practical Implicationsmentioning
confidence: 70%
“…Further, prior culinary knowledge positively impacts on the extent to which tourists seek co-creation opportunities (H6). Cognitive aspects of an experience (e.g., knowledge and learning) can act as enablers, stimulating engagement (Cordina et al, 2019;Storey and Larbig, 2018). In the cooking class context, the greater a tourist's knowledge of food production, cooking, and delivery processes, the greater their desire for co-created experiences.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…In doing so, participatory engagement could serve to stimulate social connectivity, facilitating interactions on-site, in line with extant research which promotes cultural heritage sites as "important hubs that elevate sociability" (Jafari, Taheri, & vom Lehn, 2013, p.1746. To this end, the industry should embrace Simon's (2010) suggestions on participatory and interactive design in order to stimulate visitor-visitor interactions and meaningful exchanges (Cordina, Gannon & Croall, 2019).…”
Section: Practical Implicationsmentioning
confidence: 99%